2019
DOI: 10.1016/j.eurpsy.2018.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Burnout in medical students before residency: A systematic review and meta-analysis

Abstract: Background:Applying the concept of burnout to medical students before residency is relatively recent. Its estimated prevalence varies significantly between studies. Our objective was to estimate the prevalence of burnout in medical students worldwide.Methods:We systematically searched Medline for English-language articles published between January 1, 2010 and December 31, 2017. We selected all the original studies about the prevalence of burnout in medical students before residency, using validated questionnai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
222
10
21

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 332 publications
(309 citation statements)
references
References 82 publications
22
222
10
21
Order By: Relevance
“…En particular los estudiantes de las carreras de la salud presentan niveles de baja salud mental, ansiedad y estrés, mayores que estudiantes de otras profesiones universitarias. Datos de revisiones sistemáticas demuestran que estudiantes de medicina y de enfermería, presentan mayores niveles de ansiedad que sujetos de la misma edad, y que este trastorno se presenta con más frecuencia en mujeres (13,14).…”
Section: Universitarios Rutina Diaria Y Estrésunclassified
“…En particular los estudiantes de las carreras de la salud presentan niveles de baja salud mental, ansiedad y estrés, mayores que estudiantes de otras profesiones universitarias. Datos de revisiones sistemáticas demuestran que estudiantes de medicina y de enfermería, presentan mayores niveles de ansiedad que sujetos de la misma edad, y que este trastorno se presenta con más frecuencia en mujeres (13,14).…”
Section: Universitarios Rutina Diaria Y Estrésunclassified
“…Nous souhaitons, en préambule de cet exemple, préciser que cette problématique constitue un enjeu important qu'il convient de prendre en compte. Certains des auteurs ont, par ailleurs, déjà publié sur ce sujet (Chaumette & Morvan, 2017;Frajerman, Morvan, Krebs, Gorwood, & Chaumette, 2019).…”
Section: Et Des Incompréhensions Qui En Découlentunclassified
“…Burnout among college students refers to tiredness resulting from academic demands (emotional exhaustion), having a pessimistic sense and lack of interest toward academic tasks (cynicism toward meaning of studying), and feeling of incompetency as a student (inefficacy) (Schaufeli et al, 2002;Salmela-Aro, Kiuru, Leskinen & Nurmi, 2009). Studies show that college students experience substantial levels of burnout (Frajerman et al, 2019;Jacobs & Dodd, 2003;Leupold et al, 2019;Pisarik, 2009). As it occurs with professionals, it is observed that students, who began their studies with enthusiasm, subsequently came to express a sense of disappointment, lack of energy, fatigue, feeling of emptiness or failure, low self-esteem, lack of concentration, and desire to leave their studies (Caballero-Domínguez, Gutiérrez, & Palacio Sañudo, 2015).…”
Section: Academic Burnoutmentioning
confidence: 99%
“…Academic demands are generally high and are usually accompanied with a variety of other life stressors (Lin & Huang, 2014). If they persist over time without sufficient resources and coping mechanisms to resolve them, they may result in the development of burnout syndrome (Cecil, McHale, Hart, & Laidlaw, 2014;Frajerman, Morvan, Krebs, Gorwood, & Chaumette, 2019;Leupold, Lopina, & Erickson, 2019;May, Seibert, Sanchez-Gonzalez, & Fincham, 2019;Schaufeli, Martínez, Pinto, Salanova, & Bakker, 2002;Skodova, Lajciakova, & Banovcina, 2016;Zabuska, Ginsborg, & Wasley, 2018).…”
Section: Introductionmentioning
confidence: 99%